THE INTERPLAY OF SOCIAL CAPITAL AND ENTREPRENEURIAL PERFORMANCE: A STUDY ON AGRIBUSINESS SMALL AND MEDIUM ENTERPRISES (SMES) - Nur Muttaqien Zuhri; Nurul Puspita; Muhammad Ariq Surya Antoro (Jurnal Sains Agribisnis, 2025)
The performance of small and medium-sized enterprises (SMEs), particularly in the agribusiness industry, is significantly affected by social capital. Up to this point, studies have yet to delve into the connection between social capital and the entrepreneurial performance of businesses. This research examines the impact of social capital on the sustainable entrepreneurial performance of firms. To analyze the data, the study utilizes a quantitative approach and structural equation modelling (SEM) partial least squares (PLS) with SmartPLS 3.0 software. Data for the study was gathered by distributing an online survey to 650 owners of Agribusiness SMEs in Central Java, chosen through simple random sampling. The survey used a Likert scale ranging from 1 to 7. The data analysis encompasses validity, reliability, and hypothesis testing stages. The data analysis indicated that trust does not significantly influence the entrepreneurial performance of the company. However, social norms have a positive and significant impact on the entrepreneurial performance of the company, and social networks also have a positive and significant effect. The uniqueness of this study lies in constructing a correlation model for the variables of trust, social norms, and networks associated with social capital. The practical implication of this study is to encourage the improvement of Agribusiness SMEs' performance in implementing the circular economy. The theoretical implication of this study is the creation of a new correlation model of social capital in the sustainable entrepreneurial performance of Agribusiness SMEs.